Tradisi Slamatan / Yasinan Manifestasi Nilai Sosial Keagamaan di Kedurang - Agung Wahyudi (GHAITSA : Islamic Education Journal, 2024)
Rejecting from the negative assumption of the Islam conservatif toward slametan. It necessary to bring back positive value that contain in slametan tradition. Yasinan is identified with the slametan in Kedurang, South Bengkulu that contain social-religious value as society unifier. Yasinan tradition is expected become an alternative social interaction to create peaceful society and full of harmony. Yasinan are also a moment for sharing and became unique Islam tradition until now. The purpose of this research is reveal social religion value that contain in yasinan. This study use a qualitative method with a phenomenology approach. There are two findings: firstly, as religious tradition which teach peace between members of the community and also as a means of giving alms. Secondly, as Islamic spirit booster for community when they yasinan is contain activities read the verses of Qur’an, tahlil and istighosah.